Iran: Economic revolution or recession? - Matthias Diermeier (Institut der deutschen Wirtschaft (IW), 2016)
International traders' and investors' expectations were raised after Iran had pledged to implement the landmark nuclear deal negotiated with the US, UK, France, Russia and Germany. While the Islamic Republic constitutes a trading hub with great economic potential, large amounts of goods or investment sums have yet to cross its borders. Instead, US-imposed sanctions that should have been lifted months ago de facto remain in place.
Keywords: 330